Lead as a trigger factor in the formation of endothelium dysfunction under occupational exposure to lead (Environment & Health, 2015)
Objective. We determined a character of the content of nitrogen oxide and its metabolites in blood depending on the lead concentration in the blood of electricians.Materials and methods. Monitoring result analysis by the index of lead concentration in the of 146 electricians of the PJSC Kabelnye Seti for repair and installation of cable net demonstrated that xenobiotic concentration in blood were determined in the limits of (1.34-2.31) µmol/l, in 51 persons it exceeded an upper limit of the allowable values (1.93 µmol/l).Those levels are dangerous for the workers' health. The symptoms of neurasthenic and astheno>vege> tative syndromes prevailed in the clinical finding of the workers, just those persons made up the 1-st group. In 95 of them (65%) a content of lead in blood was at the allowable level (0.96-1.93) µmol/l. According to the data by I.N. Trakhteberg et al. (1999), it pointed to the presence of the metal in the organism. Taking into account the features of clinical manifestations of the astheno>vegetative and neurasthenic syndromes, the workers with the allowable content of lead were divided into two groups: the 2-nd group constituted 46 persons with the clinical symptoms of the severe astheno> vegetative syndrome; the 3-rd group made up 49 workers with the separate symptoms of astheno> vegetative syndroms in their clinical finding. Lead concentration in the blood of the 1>st group made up (2.12 ± 0.012) µmol/l, the 2-nd group — (1.92 ± 0.013) µmol/l, the 3-rd group — (1.72 ± 0.028) µmol/l. In each group of the examined per> sons the level of lead in blood differed authentically between each other (p
Keywords: leadnitrates nitritesS nitrozotiolesdinitrosyl iron complexesmarkersdiagnosisprophylaxis